Soluble Mediators Regulating Immunity in Early Life - Pettengill, Matthew Aaron; van Haren, Simon Daniël; Levy, Ofer (Frontiers in Immunology, 2014)
Soluble factors in blood plasma have a substantial impact on both the innate and adaptive immune responses. The complement system, antibodies, and antimicrobial proteins and peptides (APPs), can directly interact with potential pathogens, protecting against systemic infection. The extracellular environment also has a critical influence on immune cell maturation, activation, and effector functions, and many of the factors in plasma, including hormones, vitamins, and purines, have been shown to influence these processes for leukocytes of both the innate and adaptive immune systems. In this review we give particular consideration to soluble mediators in plasma for which age-dependent differences in abundance may influence the ontogeny of immune function.